2014
DOI: 10.1097/ico.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subconjunctival Tocilizumab Versus Bevacizumab in Treatment of Corneal Neovascularization in Rabbits

Abstract: An antiangiogenic effect was observed after subconjunctival injection of 2.5 mg tocilizumab to an extent similar to that seen with 2.5 mg bevacizumab, which indicates that subconjunctival application of tocilizumab is effective for the inhibition of corneal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Moreover, the corneal inflammation score and corneal VEGF levels were significantly lower . In addition, compared with bevacizumab, subconjunctival injection of 2.5 mg tocilizumab showed similar effect of decreasing CNV under the same dosage …”
Section: The Drug Treatment Of Cnvmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, the corneal inflammation score and corneal VEGF levels were significantly lower . In addition, compared with bevacizumab, subconjunctival injection of 2.5 mg tocilizumab showed similar effect of decreasing CNV under the same dosage …”
Section: The Drug Treatment Of Cnvmentioning
confidence: 85%
“…[35] In addition, compared with bevacizumab, subconjunctival injection of 2.5 mg tocilizumab showed similar effect of decreasing CNV under the same dosage. [36] Ranibizumab is a recombinant humanized monoclonal antibody fragment that inhibits VEGF-A isoforms. Researches showed that topical or subconjunctival administration of ranibizumab had the effect of suppressing CNV formation.…”
Section: Anti-vegf Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited literature describing the use of voriconazole by SCo injection in horses. Reports of the use of this route with drugs other than voriconazole have proven to provide therapeutic concentrations to the anterior segment of the eye [48][49][50]. The topical 1% voriconazole treatment was considered a positive (standard treatment in clinical field) control to validate AH concentrations of voriconazole in this group of horses and as a comparison to previously published results [4].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, steroids and other anti-inflammatory drugs are widely used, but these treatments are associated with unstable efficacies and significant side effects ( 33 ). Anti-VEGF biological agents have shown effective therapeutic effects in numerous ocular diseases ( 34 36 ). However, these biological agents are accompanied by severe complications in the eye, such as delaying epithelial wound healing and persistent epithelial defects or even corneal dissolution ( 2 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%